Chronic kidney disease biomarkers in populations at risk: Results of screening study carried out in Priboj - Svetlana Krsmanović (Биомедицинска истраживања, 2018)
Introduction: Chronic kidney diseases are global health problem and thus close attention is devoted to their prevention and early detection. The aim of the study was to assess the prevalence of chronic kidney disease biomarkers in three groups at risk. Methods: The study included 77 persons divided into three groups: (1) 31 patients with hypertension that had lasted for five years; (2) 30 patients with type 2 diabetes diagnosed five or more years ago and (3) 16 examinees, aged ? 60, without hypertension and diabetes. All patients participated in the survey, after which blood pres-sure, body mass index, glucose serum level and urea and creatinine serum level were measured. Urine albumin and protein were determined by urine dipstick test and urine sediment was analyzed as well. Glomerular filtra-tion rate (GFR) was estimated by Modification of Diet in Renal Disease (MDRD) equation 4. Results: These three groups were matched for gender and more than a half of patients with hypertension and diabetes were aged ? 60 years. Among patients with diabetes, 26 patients (86.6%) had hypertension, while overweight was found in 67.7% of patients with hypertension, 76.7% of those with diabetes and 25% of exam-inees aged ? 60 years. Normal blood pressure range had more than two-thirds of patients with hypertension and diabetes, and ACEI was used by 74.2% of patients with hypertension and 80% of patients with diabetes. Fasting serum glucose level was above 6.1 mmol/L in 23 (76.6%) of patients with diabetes. GFR below 60 ml/ min/1.73m 2 had 7 (22.6%) patients with hypertension, 14 (46.7%) patients with diabetes and 3 (18.8%) persons aged ? 60 years. Pathologic albuminuria (? 20 mg/L) had 22 (61%) patients with hypertension, 25 (83.4%) pa-tients with diabetes and 10 (62.5%) examinees aged ? 60 years. Conclusion: Although the applied screening methods could overestimate the frequency of examined biomark-ers for chronic kidney disease, the results of the study confirmed the importance of regular control of kidney function in population at risk for chronic kidney disease.
Keywords: chronic kidney disease biomarkers; hypertension; diabetes; aged 60 years